Brand Awareness dan Lifestyle pada Purchase Decision Kartu Pokémon melalui Customer Satisfaction - Muhammad Aldiansyah; Muzakir Muzakir; Umar Syarifuddin; Faruq Lamusa (Studi Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This study aims to determine the influence of brand awareness and lifestyle on customer satisfaction and purchase decisions of the Pokémon Trading Card Game in Palu city. Methodology/approach: A quantitative approach was used to collect data through a survey of 80 respondents who purchased the Pokémon Trading Card Game. Partial Least Squares (PLS) analysis was employed to examine the relationships between variables. Results: This study concludes that the Purchase Decision for the Pokémon Trading Card Game in Palu is influenced mainly by Brand Awareness and Lifestyle, with Customer Satisfaction playing a supportive role. However, Lifestyle had no significant effect on Customer Satisfaction, nor did Customer Satisfaction mediate its relationship with purchase decisions. Conclusions: This study confirms that brand awareness and lifestyle are dominant factors in the purchase of Pokémon trading cards, while consumer satisfaction reinforces purchasing decisions rather than mediating the influence of lifestyle. Limitations: This study had several limitations. First, it was conducted only in Palu; therefore, the findings may not represent consumer behavior in other regions. The focus on Pokémon Trading Card Games limits the generalization to other collectible card games or entertainment products. Contribution: This study contributes by showing that brand awareness and lifestyle drive purchase decision for Pokémon Trading Card Game in Palu, with customer satisfaction reinforcing purchases, providing both theoretical insights and practical guidance for marketers.